Overview of Tawang agriculture: opportunities and challenges - Ankit; Sunil K Singh; Gaurav Singh Dhakad; Parashuram Lamani; Ajitabh Bora; Baikuntha J Gogoi; Dev Vrat Kamboj (Annals of Agricultural Research, 2024)
The biodiversity of Tawang sector, though a treasure trove in Arunachal Pradesh, however, the agrobiodiversity is limited to a few horticultural and agronomic crops owing to a very specific set of environmental conditions characterized by chilling temperatures and heavy rainfall. Despite adverse climatic conditions such as strong winds, acidic soils with undulated topography, etc., this region has a unique opportunity to grow and introduce many exotic crops of the temperate climate ofthe world under a protected cultivation system. The successful cultivation of some of the exotic vegetables such as pak choi, lettuce (loose leaf and open head type), Swiss chard, celery, parsley, red cabbage, broccoli, Chinese cabbage, etc. and strawberry among high-value crops under greenhouse cultivation has been demonstrated to the local farmers, the rate of adoption of their cultivation practices is still marginal because of poor infrastructural support, lack of awareness and input availability. Apple, kiwi, cherry, strawberry and prunes are many potential fruit crops grown commercially in temperate regions that can be introduced up to 2500m altitude of this sectorto make agriculture a profitable venture and switchto sustainable farmingfrom current subsistence farming.